ANALISIS KUANTITATIF DEVIASI PRODUKTIVITAS MASS CONCRETE PADA BASEMENT 3 - Hermanto, Jolanda Ozerlie; Linda Azhari; Mega Watty (Jurnal Teknik Sipil, 2025)
Abstract: Mass concrete pouring for raft foundations requires continuous execution to maintain structural integrity and prevent cold joints. This study aims to analyze productivity deviations in the mass concrete pouring of a 12,390 m³ raft foundation at Basement 3 of a high-rise building project in Jakarta. A descriptive quantitative approach with a case study method was employed using secondary data, including the baseline schedule, concrete pouring logs, truck mixer arrival records, and slump rejection data. Data were analyzed using S-Curve Overlay, throughput analysis, headway analysis, loss time analysis, and concurrent delay analysis. The results indicate that the actual pouring duration reached 69.3 hours, exceeding the planned duration of 53 hours by 16.3 hours (30.7%). The average actual productivity was 177.6 m³/h, which was 22.7% lower than the planned productivity of 230 m³/h. Logistical delays caused by unstable truck mixer headway accounted for the largest contribution, representing approximately 49% of the total schedule deviation. The remaining 51% resulted from concurrent operational factors, including extended pouring duration, slump rejection incidents, adverse weather conditions, equipment downtime, and performance degradation due to equipment and workforce fatigue. These findings emphasize that successful large-scale mass concrete pouring depends on the synchronization of concrete supply stability, equipment reliability, material quality control, and field resource readiness.. Keywords: mass concrete, productivity, raft foundation, headway, concurrent delay Abstrak: Pekerjaan pengecoran mass concrete pada raft foundation memerlukan pelaksanaan secara kontinu untuk menjaga integritas struktur dan mencegah terjadinya cold joint. Penelitian ini bertujuan menganalisis deviasi produktivitas pada pekerjaan pengecoran mass concrete raft foundation Basement 3 dengan volume 12.390 m³ pada proyek gedung bertingkat tinggi di Jakarta. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan metode studi kasus berdasarkan data sekunder berupa baseline schedule, concrete pouring log, logbook kedatangan truck mixer, dan data slump reject. Analisis dilakukan menggunakan metode S-Curve Overlay, throughput analysis, headway analysis, loss time analysis, dan concurrent delay analysis. Hasil penelitian menunjukkan bahwa durasi aktual pengecoran mencapai 69,3 jam, lebih lama 16,3 jam atau 30,7% dibandingkan durasi rencana 53 jam. Produktivitas rata-rata aktual tercatat sebesar 177,6 m³/jam, lebih rendah 22,7% dibandingkan produktivitas rencana sebesar 230 m³/jam. Keterlambatan logistik akibat ketidakstabilan headway armada truck mixer memberikan kontribusi terbesar, yaitu sekitar 49% dari total deviasi durasi. Sementara itu, 51% sisanya disebabkan oleh faktor operasional yang terjadi secara bersamaan, meliputi pembengkakan durasi penuangan, kejadian slump reject, gangguan cuaca, downtime peralatan, serta penurunan kinerja akibat fatigue pada alat dan tenaga kerja. Hasil penelitian menegaskan bahwa keberhasilan pengecoran mass concrete sangat bergantung pada sinkronisasi antara stabilitas suplai beton, keandalan peralatan, pengendalian mutu material, dan kesiapan sumber daya lapangan. Kata kunci: mass concrete, produktivitas, raft foundation, headway, concurrent delay